Vane with text: 'Wa ma al-nasru illa min ind Allah' ('And there is no victory but from God'); 'Lubnan 1' ('Lebanon 1'); 'Fa'inna hizb Allah hum al-ghalibun' ('The party of God are the victors'); 'Hizb Allah' ('The party of God')
Vane with text: 'Wa ma al-nasru illa min ind Allah' ('And there is no victory but from God'); 'Lubnan 1' ('Lebanon 1'); 'Fa'inna hizb Allah hum al-ghalibun' ('The party of God are the victors'); 'Hizb Allah' ('The party of God').